Distinct features between HLA-DR+ and HLA-DR− PD-1hi CXCR5– T peripheral helper cells in seropositive rheumatoid arthritis. (4th September 2020) - Yamada, Hiroki; Sasaki, Takanori; Matsumoto, Kotaro; Suzuki, Katsuya; Takeshita, Masaru; Tanemura, Shuhei; Seki, Noriyasu; Tsujimoto, Hideto; Takeuchi, Tsutomu
Abstract: Objectives: PD-1hi CXCR5– T peripheral helper (Tph) cells are newly identified pathogenic CD4 helper T cells in RA. We evaluated the usefulness of Tph cell subsets as biomarkers of RA. Methods: RA patients who visited our rheumatology department between May 2015 and September 2017 and met the 2010 ACR/EULAR classification criteria were included. We compared the correlation of DAS28-ESR between Tph cell subsets and 40 immune cell subsets. We also explored which subsets reflected the chronological changes in the disease activity after treatment. Results: Thirty-four seropositive RA patients, 11 seronegative RA patients and 34 healthy controls were included. Tph cell subsets that correlated with the DAS28-ESR were HLA-DR+ Tph cells ( rs  = 0.50, P  = 0.002), HLA-DR– Tph cells ( rs  = 0.39, P  = 0.03) and Tph1 cells ( rs  = 0.41, P  = 0.02). Among the other 40 immune cell subsets, HLA-DR+ Th1-17 cells ( rs  = 0.38, P = 0.03), activated B cells ( rs  = –0.35, P  = 0.04), plasma cells ( rs  = 0.43, P  = 0.01) and CD14++ CD16+ monocytes ( rs  = 0.36, P  = 0.04) correlated, but not strongly as HLA-DR+ Tph cells. However, MTX treatment reduced the proportion of HLA-DR+ Tph cells independently of the disease activity. In contrast, HLA-DR– Tph cells accurately reflected the change in the DAS28-ESR during MTX treatment. Conclusion: HLA-DR+ Tph cells were decreased with MTX treatment, independent of the disease activity, while HLA-DR– Tph cells reflected the disease activity accurately during the treatment.